An Analysis Of Community Satisfaction Index Towards Samsat Public Services In Bengkulu City - Syakira Maharanti Suci; Ahmad Soleh; Ida Ayu Made Ermetha Gayatri (Journal of Indonesian Management, 2022)
The community satisfaction index only applies to government agencies that provide direct services to the community. This study aims to determine the Community Satisfaction Index for SAMSAT Public Services in Bengkulu City. The analytical method used is the Community Satisfaction Index (IKM) based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 with 9 indicators namely requirements, procedures, completion time, costs/tariffs, product. Type of service, competency of implementer, behavior of implementer, handling of complaints suggestions and input, facilities and infrastructure. The data method obtained in this study was obtained directly from the questionnaire filler aimed at the respondents. In this study the questionnaire was used to collect data on community satisfaction by distributing questionnaires to the SAMSAT public services of Bengkulu City. From the results of the analysis of the Community Satisfaction Index for the SAMSAT public services of Bengkulu City is 86.955. This means that the service quality performed by SAMSAT of Bengkulu City is included in category B therefore, the service performance at SAMSAT of Bengkulu City can be said to be good because it is in the range of conversal interval values 76.61 -88.30.